The host cities perspective: An overview of the impact of COVID-19 on sporting events (Burson Cohn & Wolfe, 2020)
Over the past few weeks, throughout the world, the COVID-19 outbreak has taken the world by surprise and has brought great strain upon all parts of society including cities and organisations involved in the hosting of international sports events. In order to understand how cities around the world have been coping with the current crisis, what they expect to happen in coming weeks and what their concerns for the future are, the BCW Sports Practice developed a Host City Survey in order to collect their testimonies. This survey was sent out to an international selection of 100 host cities and was carried out over a one-week period from March 23-29, 2020. The following report outlines six key insights about the current sentiment landscape amongst host cities regarding the impact of COVID-19 on the future of sports events and on hosting strategies.